OPTIMIZATION OF PARAMETERS OF OPTICAL AND ELECTRONIC DEVICE IN THE PROCESS OF DETECTING DISTANT OBJECTS: OPTIMIZATION OF PARAMETERS OF OPTICAL AND ELECTRONIC DEVICE IN THE PROCESS OF DETECTING DISTANT OBJECTS - Getsov, Peter; Zhekov, Zhivko; Stoyanov, Stiliyan (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The process of detecting distant objects through optical and electronic device along with optical device (visir) for preliminary rough targeting has been investigated. Methods of optimization and determination of the optimal values of the basic parameters of dev ices in detecting regime for distant objects hav e been suggested.